Integrated water resources management from concept to implementation (Routledge special issues on water policy and governance, 2016)
The book includes seventeen excellent researched and documented papers that reflect the diversity of thought, ideas and experiences related to IWRM. They draw from an extensive, inclusive and geographically representative range of theoretical propositions and practical examples. The book has the objective of fostering scholarly exchange, encouraging intellectual debate and promoting the advancement of knowledge and understanding of IWRM as a concept, as a goal per se and as a strategy towards development goals.